Effects of different weed management systems on potato yield under conservation and conventional tillage systems - shahab eghbali; alireza koochaki; mehdi nassiri mahalati (پژوهشهای زراعی ایران, 2009)
In recent years, weed scientists have paid more attention towards integrated weeds management to prevent weed resistance to herbicides. To examine the effect of different weed management systems in potato, a field experiment was conducted on a strip split plots based on 3 complete randomized blocks design. Horizontal factor was two tillage systems (conservation, conventional) and vertical factor was 6 weeds control treatments (1-herbicide, 2-reduced herbicide, 3 weeding, 4-cultivator, 5-combination of 1 and 3 treatments, 6- combination of 2 and 4 treatments). Results showed that the highest yield was obtain in the weeding and cultivator treatments both in conventional and conservation tillage systems. Potato yield was not different in integrated treatments (reduced herbicide+ weeding or cultivator) compared to single treatments (full herbicide dose and reduced herbicide dose) in conventional treatment. Integrated treatment had the highest yield and the lowest weeds number and biomass. Generally, integration of mechanical weeds management with reduced herbicide dose in conservation tillage was the most successful management practice for potato weeds.